Partial repowering analysis of a wind farm by turbine hub height variation to mitigate neighboring wind farm wake interference using mesoscale simulations. (15th June 2020) - Syed, Abdul Haseeb; Javed, Adeel; Asim Feroz, Raja M.; Calhoun, Ronald
Highlights: Inter-farm wake losses intensify due to uncoordinated wind farm development. Repowering augments the power generation capacity of existing wind farms. Mesoscale simulation provides a fast repowering analysis of wind farms. Power output is increased by varying the hub height of wake affected turbines. Abstract: Repowering augments the power generation capacity of a wind farm in order to enhance the exploitation of the high mean wind speed regions. In this study, a partial repowering strategy has been discussed for an onshore commercial-scale wind farm with deteriorated performance under the influence of wakes originating from upstream wind farms. The mesoscale Weather Research and Forecasting (WRF) model with Wind Farm Parameterization has been employed to evaluate the wind speed and power deficit observed by the individual wind turbine generators. Wakes induced by the upstream wind farms are observed to cause a reduction in wind speed and power output by up to 15% and 35%, respectively. The predicted power was also validated by the observed data for each turbine generator. The hub heights of selected wind turbines with the highest power deficit are varied to alleviate the influence of upstream wind farm wake interference. Power output and wind shear profiles have been evaluated at new hub heights of 61.5 m and 100 m, and results are compared with the existing hub height turbine generators at 80 m. Power output reduced by up to 12% at the lower hub height of 61.5 m as compared to the default case, while an increase of about 13.6% is observed for the 100 m hub height case. A mean increase of 7.5% is estimated in the total wind power generation from the wind farm under evaluation. This paper presents a theoretical and engineering platform for partial repowering of wind farms with depleted generation due to inter-farm wake interaction.